Comparison of postharvest quality changes of export mango fruit from different harvest sites in Thailand - E. Yasunaga (2018)
In this study, we aim to clarify the effects of the postharvest environment of mango fruit (Mangifera indica L. 'Namdok Mai') on its physiological characteristics during distribution from Thailand to Japan. Fruit was harvested from different orchards in Thailand: Phrao, Phitsanulok and Mae Teang. The fruit quality at harvest was found to be different between the orchards. Although the hardness scores were slightly different between the orchards, the total sugar content at harvest for fruit produced in Phrao was significantly higher than the fruit produced in Phitsanulok and Mae Teang. Conversely, the content of L-AsA at harvest was the highest for fruit from Mae Teang, followed by Phrao and Phitsanulok. Three fruit quality indicators: hardness score, total sugar content and TSS, showed similar responses irrespective of harvest sites. The results confirm that different production and distribution management practices can influence the quality of mango fruit and thus impact on the price the fruit receives in both domestic and international markets.